Associations of Human Milk Oligosaccharides With Otitis Media and Lower and Upper Respiratory Tract Infections up to 2 Years: The Ulm SPATZ Health Study - Siziba, Linda P.; Mank, Marko; Stahl, Bernd; Kurz, Deborah; Gonsalves, John; Blijenberg, Bernadet; Rothenbacher, Dietrich; Genuneit, Jon (Frontiers in Nutrition, 2021)
Background: Human milk oligosaccharides (HMOs) support and concurrently shape the neonatal immune system through various mechanisms. Thereby, they may contribute to lower incidence of infections in infants. However, there is limited evidence on the role of individual HMOs in the risk of otitis media (OM), as well as lower and upper respiratory tract infections (LRTI and URTI, respectively) in children up to 2 years. Objective: To investigate whether individual HMO concentrations measured at 6 weeks of lactation were associated with risk of OM, LRTI or URTI up to 2 years in breastfed infants. Associations with OM, LRTI and URTI were determined for the most prominent human milk oligosaccharides including 13 neutral, partly isomeric structures (trioses up to hexaoses), two acidic trioses, and lactose. Design: HMO measurements and physician reported data on infections were available from human milk samples collected at 6 weeks postpartum (n=667). Associations of HMOs with infections were assessed in crude and adjusted models using modified Poisson regression. Results: Absolute concentrations (median [min, max], in g/L) of 2’-fucosyllactose (2’-FL) tended (p=0.04) to be lower, while lacto-N-tetraose (LNT) was higher in the milk for infants with OM in the 1st year of life (p=0.0046). In the milk of secretor mothers, LNT was significantly higher in the milk for infants with OM (RR [95% CI]: 0.98 [0.15, 2.60]) compared to infants without OM (RR [95% CI]: 0.76 [0.14, 2.90]) at 1 year (p=0.0019). No statistically significant milk group differences and associations were observed for OM, LRTI and URTI (p>0.0031). Conclusion: Our findings suggest that neither prominent neutral individual HMOs (ranging from 2’-FL to LNDFHs) nor acidic human milk sialyllactoses or lactose are significantly associated with a reduced or increased risk of infections in infants up to 2 years of age. Further research is needed to determine whether specific HMOs could potentially reduce the incidence or alleviated the course of distinct infections in early life.